Acute personalized habitual caffeine doses improve attention and have selective effects when considering the fractionation of executive functions. (1st December 2015) - Lanini, Juliana; Galduróz, José Carlos Fernandes; Pompéia, Sabine
Abstract : Caffeine is widely used, often consumed with food, and improves simple and complex/executive attention under fasting conditions. We investigated whether these cognitive effects are observed when personalized habitual doses of caffeine are ingested by caffeine consumers, whether they are influenced by nutriments and if various executive domains are susceptible to improvement. This was a double‐blind, placebo‐controlled study including 60 young, healthy, rested males randomly assigned to one of four treatments: placebo fasting, caffeine fasting, placebo meal and caffeine meal. Caffeine doses were individualized for each participant based on their self‐reported caffeine consumption at the time of testing (morning). The test battery included measures of simple and sustained attention, executive domains (inhibiting, updating, shifting, dual tasking, planning and accessing long‐term memory), control measures of subjective alterations, glucose and insulin levels, skin conductance, heart rate and pupil dilation. Regardless of meal intake, acute habitual doses of caffeine decreased fatigue, and improved simple and sustained attention and executive updating. This executive effect was not secondary to the habitual weekly dose consumed, changes in simple and sustained attention, mood, meal ingestion and increases in cognitive effort. We conclude that the morning caffeine "fix" has positive attentional effects and selectively improved executive updating whether or not caffeine is consumed with food. Copyright © 2015 John Wiley & Sons, Ltd.